Socio-technical barriers to domestic hydrogen futures: repurposing pipelines, policies, and public perceptions - Gordon, Joel A.; Balta-Ozkan, Nazmiye; Nabavi, Seyed Ali (Elsevier, 2023)
The feasibility of the global energy transition may rest on the ability of nations to harness hydrogen's potential for cross-sectoral decarbonization. In countries historically reliant on natural gas for domestic heating and cooking such as the UK, hydrogen may prove critical to meeting net-zero targets and strengthening energy security. In response, the UK government is targeting industrial decarbonization via hydrogen, with parallel interest in deploying hydrogen-fueled appliances for businesses and homes. However, prospective hydrogen futures, and especially the domestic hydrogen transition, face multiple barriers which reflect the cross-sectoral dynamics of achieving economies of scale and social acceptance. Addressing these challenges calls for a deep understanding of socio-technical factors across different scales of the hydrogen economy. In response, this paper develops a socio-technical systems framework for overcoming barriers to the domestic transition, which is applied to the UK context. The paper demonstrates that future strategies should account for interactions between political, techno-economic, technical, market, and social dimensions of the hydrogen transition. In parallel to techno-economic feasibility, the right policies will be needed to create an even playing field for green hydrogen technologies, while also supporting stakeholder symbiosis and consumer buy-in. Future studies should grapple with how an effective repurposing of pipelines, policies, and public perceptions can be aligned to accelerate the development of the hydrogen economy, with maximum net benefits for society and the environment.
Keywords: Domestic hydrogen transition; Socio-technical systems; Techno-economic barriers; Decarbonization; Public perceptions